KOMANDIRLAR IMIJINI RIVOJLANTIRISHNING IJTIMOIY-PSIXOLOGIK OMILLARI - Ravshanov Lochinbek Urinovich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, the socio-psychological factors of the development of the image of commanders were analytically described. Emphasis was placed on the socio-psychological features of the image. The development of socio-psychological characteristics of the commander's image is based on the provision of positive military management.